Faster insulin action is associated with improved glycaemic outcomes during closed‐loop insulin delivery and sensor‐augmented pump therapy in adults with type 1 diabetes. Issue 10 (23rd June 2017) - Ruan, Yue; Thabit, Hood; Leelarathna, Lalantha; Hartnell, Sara; Wilinska, Malgorzata E.; Tauschmann, Martin; Dellweg, Sibylle; Benesch, Carsten; Mader, Julia K.; Holzer, Manuel; Kojzar, Harald; Evans, Mark L.; et al.
Abstract : We aimed to evaluate the relationship between insulin pharmacodynamics and glycaemic outcomes during closed‐loop insulin delivery and sensor‐augmented pump therapy. We retrospectively analysed data from a multicentre randomized control trial involving 32 adults with type 1 diabetes receiving day‐and‐night closed‐loop insulin delivery and sensor‐augmented pump therapy over 12 weeks. We estimated time‐to‐peak insulin action ( t max, IA ) and insulin sensitivity ( S I ) during both interventions, and correlated these with demographic factors and glycaemic outcomes. During both interventions, t max, IA was positively correlated with pre‐ and post‐intervention HbA1c ( r  = 0.50‐0.52, P  < .01) and mean glucose ( r  = 0.45‐0.62, P  < .05), and inversely correlated with time sensor glucose, which was in target range 3.9 to 10 mmol/L ( r  = −0.64 to −0.47, P  < .05). Increased body mass index was associated with higher t max, I and lower S I (both P  < .05). During closed‐loop insulin delivery, t max, IA was positively correlated with glucose variability ( P  < .05). Faster insulin action is associated with improved glycaemic control during closed‐loop insulin delivery and sensor‐augmented pump therapy.